(untitled) (Journal of Global Arts Studies, 2024)
Background: In the context of the era of intangible cultural heritage protection and cultural tourism integration, China and local governments at all levels have increased their efforts to protect and develop folklore, and the trend of legend landscaping has gradually emerged. As an important part of traditional culture, folk legends have unique cultural value and historical significance. Objective: In order to deeply explore the cultural value of the countryside, the author conducted a field study and analysed in detail the inspiration of folklore culture on rural landscape design. On this basis, the author further discusses how to effectively integrate folklore culture into rural landscape design to achieve the cultural heritage of landscape in the context of the new situation. Methods: Combining literature method, case study method and field research method to explore the landscape heritage of folklore under the construction of beautiful countryside. Results: This paper takes Chinese folklore stories as the carrier, landscape modelling, materials and colours as the realization path, and promotes the creative transformation and innovative development of folklore inheritance mechanism. It is conducive to deepening and expanding the perspective of intangible cultural heritage research. Conclusion: Folklore has an irreplaceable value in rural construction. It can not only enrich the cultural heritage of rural landscape and enhance the attractiveness of the countryside, but also promote the sustainable development of folklore through the inheritance of landscape. It provides new ideas and methods for rural construction, and has positive significance for the protection and inheritance of folklore.